Respuesta :
Hi,
L = (1/6)x - 1
P = 2x + 2L = 2x + (2/6)x - 2
P= (7/3)x - 2
x being the width.
Hope this helps!
L = (1/6)x - 1
P = 2x + 2L = 2x + (2/6)x - 2
P= (7/3)x - 2
x being the width.
Hope this helps!
Answer:
The expressions represents the perimeter of the rectangle is [tex]\frac{7}{3}x-2[/tex] .
Step-by-step explanation:
Let the width of the rectangle be x
We are given that The length of a rectangle is one unit shorter than one-sixth of the width x
Length of the rectangle = [tex]\frac{1}{6}x-1[/tex]
Perimeter of rectangle = [tex]2(Length +Breadth)[/tex]
= [tex]2(\frac{1}{6}x-1+x)[/tex]
= [tex]2(\frac{7}{6}x-1)[/tex]
= [tex]\frac{7}{3}x-2[/tex]
Hence The expressions represents the perimeter of the rectangle is [tex]\frac{7}{3}x-2[/tex] .